Determining housing affordability for young professionals in Klang Valley, Malaysia: residual income approach - Sohaimi,, Nor Suzylah; Abdullah, Alias; Shuid, Syafiee (Malaysian Institute of Planners, 2018)
Underprivileged young professionals in housing affordability are prone to an adverse effect on their well-being. This article empirically examines housing affordability among young professionals aged between 25 and 35 years old who work or live in Klang Valley. Young professionals in this paper refer to young graduates with at least a Bachelor’s degree and are registered to professional institutions such as the Institution of Engineers Malaysia (IEM), Malaysian Institute of Architects (MIA), Malaysian Institute of Planners (MIP), and Royal Institution of Surveyor Malaysia (RISM). The aim of this study is to measure housing affordability based on residual income approach and to identify the attribute that affects young professionals’ housing affordability. Adequacy of household income for monthly mortgage or rent as well as other non-housing goods is reflecting for housing affordability. Attributes namely occupation, the presence of children, household expenditure, transportation cost, vehicle instalment, education loan, and household income are analysed by using binary logistic regression. 264 respondents who are either a homeowner, tenant, or parental home resident were selected by using simple random sampling. The survey data were collected through the professional institutions respectively. The study found that only presence of children, occupation of urban planner and education loan III (not taking a loan) were insignificant to the model.